A randomized, double-blind comparison of nadifloxacin 1% cream alone and with benzoyl peroxide 5% lotion in the treatment of mild to moderate facial acne vulgaris [Hafif-orta şiddetli akne vulgaris yüz tutulumu tedavisinde nadifloksasinin tek başına ve benzoil peroksit ile birlikte kullanımının karşılaştırılması] - (:unkn) unknown (Marmara University, 2013)
Objective: To compare the efficacy of nadifloxacin alone and with benzoyl peroxide in the treatment of mild to moderate facial acne vulgaris. Patients and Methods: This double-blind, randomized study was conducted in a total of 93 acne patients, with at least 10 inflammatory lesions, but no more than 3 nodules or cysts on the face. All patients were instructed to apply nadifloxacin 1% cream twice daily and randomized to apply either benzoyl peroxide 5% lotion or its vehicle once daily for 8 weeks. Results: The mean percent reduction in inflammatory lesions were 22.08% in the nadifloxacin group (n=46) and 53.5% in the nadifloxacin+benzoyl peroxide group (n=47). Five (10.9%) patients in the nadifloxacin group and 18 (38.3%) patients in the nadifloxacin+benzoyl peroxide group achieved a 50% and greater reduction in the inflammatory lesion count. Conclusion: Both treatment regimens were statistically effective, but a significantly greater reduction of the inflammatory lesions was seen in the nadifloxacin+benzoyl peroxide group. The number of patients who achieved a 50% and greater reduction in inflammatory lesion count was significantly higher in the nadifloxacin+benzoyl peroxide group. Both treatment regimens were well tolerated with mild side effects.
Keywords: Acne; Benzoyl peroxide; Nadifloxacin